1995
DOI: 10.1074/jbc.270.42.24707
|View full text |Cite
|
Sign up to set email alerts
|

The Stoichiometry of the Cytochrome P-450-catalyzed Metabolism of Methoxyflurane and Benzphetamine in the Presence and Absence of Cytochrome b5

Abstract: The complete stoichiometry of the metabolism of the cytochrome b 5 (cyt b 5 )-requiring substrate, methoxyflurane, by purified cytochrome P-450 2B4 was compared to that of another substrate, benzphetamine, which does not require cyt b 5 for its metabolism. Cyt b 5 invariably improved the efficiency of product formation. That is, in the presence of cyt b 5 a greater percentage of the reducing equivalents from NADPH were utilized to generate substrate metabolites, primarily at the expense of the side product, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
83
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 67 publications
8
83
0
1
Order By: Relevance
“…Wild type cyt b 5 caused a 6-fold stimulation of the rate of fluoride formation from 0.21 Ϯ 0.03 nmol of F Ϫ min Ϫ1 nmol of cyt P450 Ϫ1 in the absence of cyt b 5 to 1.23 Ϯ 0.2 nmol min Ϫ1 nmol of cyt P450 Ϫ1 with cyt b 5 . These results are similar to the rate of methoxyflurane metabolism observed in previous studies (7,9). Replacing the conserved residues Pro 95 and Lys 94 with alanines and reversing the amino acid sequence of the linker region did not significantly alter the rate of F Ϫ formation.…”
Section: Construction and Expression Of Mutant Cyts B 5 With Linker Rsupporting
confidence: 79%
See 3 more Smart Citations
“…Wild type cyt b 5 caused a 6-fold stimulation of the rate of fluoride formation from 0.21 Ϯ 0.03 nmol of F Ϫ min Ϫ1 nmol of cyt P450 Ϫ1 in the absence of cyt b 5 to 1.23 Ϯ 0.2 nmol min Ϫ1 nmol of cyt P450 Ϫ1 with cyt b 5 . These results are similar to the rate of methoxyflurane metabolism observed in previous studies (7,9). Replacing the conserved residues Pro 95 and Lys 94 with alanines and reversing the amino acid sequence of the linker region did not significantly alter the rate of F Ϫ formation.…”
Section: Construction and Expression Of Mutant Cyts B 5 With Linker Rsupporting
confidence: 79%
“…It is unlikely that mutation of the cyt b 5 linker region alters the relative formation of the two products, as recent modeling studies have shown that, in cyt P450 2E1, the preferential metabolism of methoxyflurane to methoxydifluroacetic acid is the result of differences in the relative activation energy required for H atom extraction rather than favorable substrate binding conformations (31). In addition, the relative amounts of methoxyflurane products formed by cyt P450 2B4 are the same in the presence and absence of cyt b 5 (7). These studies indicate that the observed reduction in F Ϫ formation caused by mutation of the cyt b 5 linker region is the result of an attenuation in the overall metabolism of methoxyflurane rather than a selective decrease in O-demethylation relative to dechlorination.…”
Section: Construction and Expression Of Mutant Cyts B 5 With Linker Rmentioning
confidence: 61%
See 2 more Smart Citations
“…Some of the products formed by these enzymes have also been implicated as causative agents in a number of cancers (Gonzales & Gelboin, 1994;Shimada et al, 1996). Intermediates involved in dioxygen activation have been proposed (Fruetel et al, 1992, Gruenke et al, 1995, Loida & Sligar, 1993 from the production of superoxide or peroxide upon loss of catalytic efficiency. The mechanism of dioxygen activation is the least understood step in P450 catalysis (Figure 1), which begins with the reduction of the dioxygen complex (oxy-P450, 4 in Figure 1).…”
mentioning
confidence: 99%